Analysis Of Working Capital Turnover To Optimize Profit Growth In Perusahaan Daerah Air Minum (PDAM) Tirta Malem Kabanjahe - Saur Melianna; Winarto; Kristanty M N Nadapdap; Tri Dharma Sipayung; Tiur Rajagukguk; Rahel Junita Nainggolan; Pupu Sulayas Br Munthe (Program Studi Akuntansi Universitas Simalungun, 2024)
This research aims to analyze the working capital turnover of the Perusahaan Daerah Air Minum (PDAM) Tirta Malem Kabanjahe to optimize profit growth in the five year period (2015-2019). The data analysis method starts from collecting data, analyzing data, and drawing conclusions. The research results show that the working capital turnover of the Perusahaan Daerah Air Minum (PDAM) Tirta Malem Kabanjahe cannot be said to be optimal, because the working capital the company has each year is negative. This tendency can be caused by the company's current debt continuing to increase and cannot be met or financed by current assets. This indicates that the company's sales activities still involve a lot of current debt. Profit growth experienced fluctuations which tended to be significant as a result of the losses experienced by the company during 2015, 2017 and 2018. The working capital turnover of the Perusahaan Daerah Air Minum (PDAM) Tirta Malem Kabanjahe has not been able to optimize the company's profit growth